Nucleic Acids - Walker, John M.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 1984)
In recent years there has been a tremendous increase in our understanding of the functioning of the cell at the molecular level. This has been achieved in the main by the invention and development of new methodology, parti- larly in that area generally referred to as "genetic en- neering". While this revolution has been taking place in the field of nucleic acids research, the protein chemist has at the same time developed fresh methodology to keep pace with the requirements of present day molecular bi- ogy. Today's molecular biologist can no longer be content with being an expert in one particular area alone. He/she needs to be equally competent in the laboratory at h- dling DNA, RNA, and proteins, moving from one area to another as required by the problem he/she is trying to solve. Although many of the new techniques in molecular biology are relatively easy to master, it is often difficult for a researcher to obtain all the relevant information nec- sary for setting up and successfully applying a new te- nique. Information is of course available in the research l- erature, but this often lacks the depth of description that the new user requires. This requirement for in-depth pr- tical details has become apparent by the considerable - mand for places on our Molecular Biology Workshops held at Hatfield each summer.
The Burton Assay for DNA -- DABA Fluorescence Assay for Submicrogram Amounts of DNA -- Preparation of “RNase-Free” DNase by Alkylation -- The Isolation of Satellite DNA by Density Gradient Centrifugation -- The Isolation of High Molecular Weight Eukaryotic DNA -- Preparation of Lyophilized Cells to Preserve Enzyme Activities and High Molecular Weight Nucleic Acids -- Agarose Gel Electrophoresis of DNA -- Autoradiography of Gels Containing 32P -- Detection of Specific DNA Sequences—The Southern Transfer -- The Extraction and Isolation of DNA from Gels -- One-Dimensional Electrophoresis of Nucleic Acids in Agarose Using Denaturation with Formaldehyde and Identification of 3H-Labeled RNA by Fluorography -- Gel Electrophoresis of RNA in Agarose and Polyacrylamide Under Nondenaturing Conditions -- The Extraction of Total RNA by the Detergent and Phenol Method -- RNA Extraction by the Proteinase K Method -- RNA Extraction by the Guanidine Thiocyanate Procedure -- The Purification of Poly(A)-Containing RNA by Affinity Chromatography -- Messenger RNA Fractionation on Neutral Sucrose Gradients -- The Estimation of mRNA Content by Poly(U) Hybridization -- DNA Directed in Vitro Protein Synthesis with Escherichia coli S-30 Extracts -- In Vitro Translation of Messenger RNA in a Wheat Germ Extract Cell-Free System -- In Vitro Translation of Messenger RNA in a Rabbit Reticulocyte Lysate Cell-Free System -- Immunoprecipitation of in Vitro Translation Products with Protein A Bound to Sepharose -- In Vitro Continuation of RNA Synthesis Initiated in Vivo -- Synthesis of Double-Stranded Complementary DNA from Poly(A)+mRNA -- Plasmid DNA Isolation by the Cleared Lysate Method -- Plasmid DNA Isolation (Sheared Lysate Method) -- Small-Scale Plasmid DNA Preparation -- Preparation of Chromosomal DNA from E. coli -- Preparation and Assay of Phage Lambda -- Preparation of Phage Lambda DNA -- The Use of Restriction Endonucleases -- Ligation of DNA with T4 DNA Ligase -- The Use of Alkaline Phosphatase to Prevent Vector Regeneration -- Bacterial Transformation -- Bacterial Transformation (Kushner Method) -- In Vitro Packaging of DNA -- Yeast Transformation -- Radiolabeling of DNA by Nick Translation -- Radiolabeling of DNA Using Polynucleotide Kinase -- Radiolabeling of DNA with 3? Terminal Transferase -- Radiolabeling of DNA with the Klenow Fragment of DNA Polymerase -- Identification of Recombinant Plasmids by In Situ Colony Hybridization -- Identification of Recombinant Phages by Plaque Hybridization -- Plasmid Screening Using Single Colony Lysates -- Immunological Detection of Gene Expression in Recombinant Clones -- The Isolation of Minicells -- The Isolation of Maxicells -- The Identification of Gene Products in Minicells and Maxicells -- Molecular Cloning in Bacteriophage Lambda and in Cosmids -- DNA Transformation of Mammalian Cells -- Chemical Cleavage (Maxam and Gilbert) Method for DNA Sequence Determination -- Gel Electrophoretic Analysis of DNA Sequencing Products -- DNA Sequence Determination Using Dideoxy Analogs.
Keywords: Biochemistry; Biochemistry, general